Fostering Lecturers’ Teaching Creativity through Games - Sokhira Linda Vinde (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2019)
The purpose of this study is to see and analyze the use of games in fostering lecturers’ creativity at Language Development Center of IAIN Padangsidimpuan. The investigation in this study covers several points i.e. what games do the lecturers apply in teaching, how do they create the games, and what are the advantages of using games in teaching? This is a type of qualitative descriptive study in which it focuses on analyzing the data in depth in a form of data elaboration and generalization. This study was done at Language Development Center of IAIN Padangsidimpuan. Ten lecturers were chosen as participants of this study. Then, in collecting the data, interview and observation were used. After that, the data were analyzed descriptively in form on data elaboration and narration. Moreover, it was found that games could foster lecturers’ creativity in teaching, and there were many kinds of games that were applied by lecturers such as True/False, Cards, Pictures and Drawing, Guessing, and Miming. Finally, it was also found that there were many advantages derived from using games i.e. (1) It improves lecturers’ confidence, (2) It also can create communicative teaching and learning, and (3) It can increase the use of media and make the media more interesting.